Review on Neural Network Based Approach Towards English Handwritten Alphanumeric Characters Recognition - Bohra, Sneha U; Ingole, P V. Ingole (International Journal of Computer Sciences and Engineering, 2013)
Handwritten Character recognition is one of the active and challenging areas of research in the intense field of Image Processing and Pattern recognition. It has large number of applications which includes, processing of bank cheques, reading aid for blind, conversion of any hand written document into digital form and many more. The main reason behind the activeness of the field are the challenges like the variation and distortion of handwritten characters, different style of writing and also the variety of scripts available across the entire world. This paper provides a brief review of the systems which implements various methodologies to recognize handwritten English characters.